RISK MANAGEMENT IN MARITIME HIGHER EDUCATION INSTITUTIONS - Veronika Saragih (Jurnal Penelitian Samudra, 2026)
Maritime higher education institutions face complex and multidimensional risks arising from academic activities, operational processes, maritime training practices, safety requirements, and regulatory compliance. Unlike conventional higher education institutions, maritime colleges are required to manage risks associated with shipboard training, simulators, laboratories, cadet discipline, and international maritime standards. This study aims to analyze the implementation of risk management in maritime higher education institutions and identify key risk categories, mitigation strategies, and governance mechanisms. Using a qualitative literature review approach, this study synthesizes findings from academic journals, international maritime organization reports, and regulatory frameworks published between 2020 and 2025. The results indicate that effective risk management in maritime higher education requires an integrated framework encompassing academic risk, operational risk, safety risk, compliance risk, and reputational risk. Institutional leadership commitment, risk-based governance, and digital risk monitoring systems emerge as critical success factors. This study contributes to the development of a structured risk management model tailored to the unique characteristics of maritime higher education institutions.